Dopamine downregulation in novel rodent models useful for the study of postpartum depression - Rincón-Cortés, Millie; Grace, Anthony A. (Frontiers in Behavioral Neuroscience, 2022)
Postpartum depression (PPD) is the most common psychiatric disorder following childbirth and is characterized by maternal mood disturbances, impaired maternal responses, and disrupted caregiving- all of which negatively impact offspring development. Since PPD has detrimental consequences for both mother and child, clinical and preclinical research has focused on identifying brain changes associated with this disorder. In humans, PPD is linked to dysregulated mesolimbic dopamine (DA) system function and altered neural responses (i.e., decreased reward-related activity) to infant-related cues, which are considered hallmark features of PPD. In accordance, rodent models employing translational risk factors useful for the study of PPD have demonstrated alterations in mesolimbic DA system structure and function, and these changes are reviewed here. We also present two novel rodent models based on postpartum adversity exposure (i.e., pup removal, scarcity-adversity) which result in PPD-relevant behavioral changes (e.g., disrupted mother-infant interactions, deficits in maternal behavior, depressive-like phenotypes) and attenuated ventral tegmental area (VTA) DA neuron activity consistent with a hypodopaminergic state. Furthermore, we highlight open questions and future directions for these rodent models. In sum, human and rodent studies converge in showing blunted mesolimbic DA function (i.e., DA downregulation) in PPD. We propose that reduced activity of VTA DA neurons, resulting in downregulation of the mesolimbic DA system, interferes with reward-related processes necessary for maternal motivation and responsiveness. Thus, the mesolimbic DA system may constitute a therapeutic target for ameliorating reward-related deficits in PPD.